Car access and long-term poverty exposure: Evidence from the Moving to Opportunity (MTO) experiment. (December 2017) - Blumenberg, Evelyn; Pierce, Gregory
Abstract: The U.S. Housing and Urban Development Department designed the landmark Moving to Opportunity (MTO) Experiment for Fair Housing Voucher Program to help low-income households move out of and stay out of concentrated poverty. The program was designed based on the assumption that households benefit from living in higher-opportunity neighborhoods. Early evaluations of the MTO program, however, showed minimal gains for participant families. One explanation for these findings is the short length of time which MTO families typically spent in lower-poverty neighborhoods; the positive effects of longer-term exposure to low-poverty neighborhoods appear more promising. In this study we examine the role of automobiles in increasing the length of time that MTO households remain in lower-poverty neighborhoods over a much longer period than previous studies, 1994–2010. A growing body of research suggests that automobiles provide households with better access to opportunities than other modes of travel, particularly in neighborhoods with lower poverty rates in more dispersed urban environments. We find that automobile access reduces households' neighborhood poverty exposure by between 3% and 4%, and automobile access trails only successful lease-up among policy-relevant factors in reducing exposure. Therefore, to maximize the effects of housing mobility programs, we suggest that voucher receipt ought to be paired with policies to increase participants' access to automobiles.